Hubungan Pengetahuan dan Pola Asuh Ibu dengan Status Gizi Bayi Usia 0-12 Bulan di wilayah Kerja Puskesmas Batusura’ Tahun 2023 - Kartika Asli (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2023)
The toddler period is also known as the "golden age," which falls within a crucial phase of child growth and development. However, during this period, toddlers constitute a nutritionally vulnerable group. Failure to navigate this period effectively may cause children to miss their opportunity for a golden phase of growth and development. This study aims to determine the relationship between maternal knowledge and parenting styles with the nutritional status of infants aged 0-12 months. Method: The research design employed is an Analytical Survey with a Cross-Sectional Study approach. All mothers with infants or toddlers visiting the Batusura’ Health Center between March and June 2023 were included. A purposive sampling technique was utilized, resulting in 64 respondents. Data collection was carried out using questionnaire sheets. The collected data were subsequently processed and analyzed using SPSS Statistics version 25 and subjected to Chi-Square tests. The findings of this study reveal a relationship between maternal knowledge and infant nutritional status, with a p-value of ρ = 0.004. Furthermore, a connection between maternal parenting styles and infant nutritional status was observed, with a p-value of ρ = 0.008. Conclusion: A significant relationship exists between maternal knowledge and parenting styles with nutritional status.